Linking Employee Stakeholders to Environmental Performance: The Role of Proactive Environmental Strategies and Shared Vision - Alt, Elisa (Journal of business ethics, 2015)
Drawing on the natural-resource-based view (NRBV), we propose that employee stakeholder integration is linked to environmental performance through firms’ proactive environmental strategies, and that this link is contingent on shared vision. We tested our model with a cross-country and multi-industry sample. In support of our theory, results revealed that firms’ proactive environmental strategies translated employee stakeholder integration into environmental performance. This relationship was pronounced for high levels of shared vision. Our findings demonstrate that shared vision represents a key condition for advancing the corporate greening agenda through proactive environmental strategies. We discuss implications for the CSR and the environmental management literatures, with a particular focus on the NRBV and stakeholder integration debates.